Business, politics, and the state in Africa : challenging the orthodoxies on growth and transformation - Kelsall, Tim, 1970- (Zed Books, 2013)
Drawing on studies of Rwanda, Ethiopia, Tanzania and Ghana this book provides a new theory of the polticial and institutional conditions required for growth in Africa.